2022
DOI: 10.52337/pjer.v5i2.529
|View full text |Cite
|
Sign up to set email alerts
|

Call for Teaching Grammar: a Comparison of Wbi and Traditional Method

Abstract: The advent of computer in general and internet in particular has opened new avenues for learning language. Computer Assisted Language Learning (CALL) is considered highly effective for language learning as technology creates a student centered environment, increases learner autonomy, and results in higher learning outcomes. This study investigated if CALL using Web Based Instruction (WBI) as a tool is more beneficial than the traditional method for teaching English grammar to undergraduate students in Pakistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…There is also a shortage of qualified persons. (schwab et al, 2011;Zaman et al, 2022).these concerns have been in our country since 1959 and have remained ignored in our educational policies since 1970, 1972, 1979, 1992, and 1998. The policy report and the implementation process to fulfill the policy objectives contain inconsistencies.…”
Section: Introductionmentioning
confidence: 97%
“…There is also a shortage of qualified persons. (schwab et al, 2011;Zaman et al, 2022).these concerns have been in our country since 1959 and have remained ignored in our educational policies since 1970, 1972, 1979, 1992, and 1998. The policy report and the implementation process to fulfill the policy objectives contain inconsistencies.…”
Section: Introductionmentioning
confidence: 97%
“…Learning which resources to utilise and how to instruct others to use them requires practise. Classroom management is an essential part of education, and teachers can use management strategies to boost their students' academic performance (Carter & Nunan, 2001;Raza et al, 2023;Zaman et al, 2022). Although monitoring is an important step in the ongoing effort to enhance teaching and learning methods.…”
Section: Introductionmentioning
confidence: 99%
“…According to earlier research studies conducted in Turkey, career barriers, perceived professional social support, and levels of hopelessness among female teachers are all related (Klavuz & Nand, 2022).In a similar vein, research in Pakistan has revealed a number of obstacles to women's careers in teaching, including social standards, gender disparity, and a lack of family support (Tatlah, et al, 2018).Comparative studies have also looked at job satisfaction, teaching methods, and variations in English language usage between teachers in public and private schools (Hameed et al, 2018;Rasool, et al, 2021;Zaman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%